School Counseling Intervention Research: A 10-Year Content Analysis of ASCA- and ACA-Affiliated Journals. Issue 1 (January 2019) - Griffith, Catherine; Mariani, Melissa; McMahon, H. George; Zyromski, Brett; Greenspan, Scott B.
Authors performed a content analysis of school counseling–related intervention research in 21 journals affiliated with the American Counseling Association and the American School Counselor Association across the 10-year span of 2006–2016. Results indicated that minimal school counseling intervention research articles were published ( N = 53) in these 21 journals during that time period and that most studies were quasi-experimental, single-group, pre-/posttest design with a fairly small N, raising questions about validity and generalizability of findings. We discuss implications for practice and future research.